Ramie degum liquor: Wastage bio-macromolecule for making thermally stable functionalize polyester fabric. (June 2022) - Bhowmick, M.; Basak, S.; Samanta, Kartick K
Highlights: Degum liquor of ramie fibre, a purely wastage product has been explored for coating on the polyester fabric. Treated fabric showed LOI value of 27 and also addressed the dangerous melt dripping phenomenon of the synthetic polymer. Treated polyester fabric showed high char mass retention and lower rate of weight degradation. Physical properties of the treated fabric also remain unchanged after completion of the treatment. Pectin, lignin, hemicellulose, tannin present in the degum liquor responsible for flame retardancy action of polyester. Abstract: Decorticated ramie fibre has been degummed with alkali based formulation and the wastage degummed liquor has been applied on the polyester fabric at different concentrations by following padding technique. Degummed liquor has been characterized by using Liquid chromatography mass spectroscopy (LCMS), Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Thermo-gravimetry (TG) analysis to understand the major chemical groups present in it and its thermal behavior. Chromatography results revealed the presence of different polyphenols, pectin, tannin based compound in the degum liquor. TG curve of degum liquor reveals almost 50% mass retention at 500°C. Treated polyester fabric showed almost 40% more limiting oxygen index (LOI) as compared to the control fabric. In addition of it, melt dripping property of the treated polyester fabric also has been stopped with lower shrinkage during combustion. TG analysis of the said fabric showed 20–25% more char mass retention and lower rate of weight loss as compared to the control one. Char morphology of the control and the treated fabric was also examined and analyzed in detail. Besides, a mechanism lies behind the flame retardancy of the polyester fabric also has been postulated with the composition of the chemical compound present in the wastage liquor. It was found that high molecular weight phenolic components, pectin, natural coloring matter, tannin based polyphenols etc. present in the degum liquor playing a major role behind thermal stability. Lastly, tensile and physical properties of the treated fabric also have been measured and analytically compared with the untreated polyester.